2016
DOI: 10.1016/j.bbamem.2015.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of lipid membrane structure and dynamics by diacylglycerols with unsaturated chains

Abstract: Diacylglycerols (DAGs) with unsaturated acyl chains play many important roles in biomembranes, such as a second messenger and activator for protein kinase C. In this study, three DAGs of distinctly different chain unsaturations (i.e. di16:0DAG (DPG), 16:0-18:1DAG (POG), and di18:1DAG (DOG)) are studied using atomistic MD simulation to compare their roles in the structure and dynamics of 16:0-18:1phosphatidylcholine (POPC) membranes. All three DAGs are able to produce the so-called 'condensing effect' in POPC m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 67 publications
2
38
0
Order By: Relevance
“…4 b ), demonstrating that DAG promotes the ordering of lipid acyl chains. A similar increase of membrane lipid ordering in the presence of DAG was reported ( 15 , 50 ). Cholesterol is also known to be one of the most effective molecules in the cell membranes to cause lipid ordering.…”
Section: Discussionsupporting
confidence: 85%
“…4 b ), demonstrating that DAG promotes the ordering of lipid acyl chains. A similar increase of membrane lipid ordering in the presence of DAG was reported ( 15 , 50 ). Cholesterol is also known to be one of the most effective molecules in the cell membranes to cause lipid ordering.…”
Section: Discussionsupporting
confidence: 85%
“…Penetration of DAG molecules into PC bilayers has been reported for several lipid mixtures, where it is commonly shown to lead to an increase in bilayer organization and thickness. 9 , 17 , 21 , 32 In MD simulations of 10% DAG and 10% PA systems, we observed no significant change in the overall bilayer thickness (∼39.2 Å) over the course of a 200 ns simulation, although there is 0.3 Å higher fluctuation in the DAG system ( Figure S6 ). This is comparable with SANS experiments, which showed the PC bilayer thickness to be 36 Å at time t = 0 ( Table 1 ).…”
Section: Resultsmentioning
confidence: 88%
“… 20 A recent single-concentration study of the diacylglycerols DPG, POG, and DOG in POPC membrane bilayers reported that this decrease in lateral diffusion of lipids is proportional to the level of DAG unsaturation. 21 …”
Section: Introductionmentioning
confidence: 99%
“…Other research has shown that DAGs can be highly localised in specific areas of the membrane during cellular growth (29), potentially increasing the damage to the lamellar structure of the membrane. However, low concentrations of DAGs can replace ERG in membrane microdomains (30), making the membrane more rigid (11). Besides the membrane structure itself, it is possible that transformants have a different rate of acetic acid efflux, which could influence the net influx of acetic acid.…”
Section: Storage Lipidsmentioning
confidence: 99%
“…The main protein in the PM is Pma1 (10), and the main sterol is ergosterol (ERG). The latter can reside partly in the interior of the lipid bilayer, increasing membrane rigidity (11). The lipid fraction of the S. cerevisiae PM consists of several of lipids, and a simplified schematic of S. cerevisiae lipid metabolism is shown in Figure 1B.…”
Section: Introductionmentioning
confidence: 99%